Teaching in Times of COVID-19 Pandemic in Two Peripheral Greek Universities: Lessons Learned from Students’ Experiences and Opinions - Raikou, Natassa; Kaltsidis, Chris; Kedraka, Katerina; Karalis, Thanassis (International Journal of Educational Studies, 2020)
COVID-19 pandemic has affected many aspects of social and economic life, including the educational sector. While each level of education faces its unique challenges, for the Higher Education the pandemic may act as the catalyst triggering a learning revolution. In the current study, which took place in April-May 2020, in the middle of lockdown in Greece, students from two regional Universities in Greece who participated pointed out that the Covid-19 pandemic disturbed their studies, even though their institutions managed to turn very quickly and successfully to distance learning. Despite the fact they are both old enough to handle the online work and technologically savvy enough to navigate new, digital tools and methods, a lot of anxiety, doubts and concerns arose. The main finding is that Greek students found it difficult to handle the lack of the everyday campus life and interaction with their fellow students and teachers, a lesson learnt for faculty to add pedagogically interactive tools, experiences, and ideas to stimulate students? learning engagement.